1974
DOI: 10.1002/bip.1974.360130507
|View full text |Cite
|
Sign up to set email alerts
|

The interaction of β‐cyclodextrin with dinucleoside phosphates

Abstract: Circular dichroism studies of the interaction of β‐cyclodextrin with a series of eight dinucleoside phosphates, and with 3′‐AMP are reported. From results with ApU and ApA, it is shown that β‐cyclodextrin binding is sensitive to dinucleoside stacking in approximately the same way as optical measures of stacking. Some qualitative uses of β‐cyclodextrin binding are suggested, based on the fact that the change in the CD spectrum caused by cyclodextrin binding is unique to each of the dinucleosides studied. Hoffma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

1980
1980
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 15 publications
1
12
0
Order By: Relevance
“…Formoso reported similar binding trends with β-CyD through the use of circular dichroism (CD) spectroscopy in a sodium phosphate buffered solution at pH 7. 775,776 Using this method, a 1:1 binding constant of 41 M- 1 was measured for the complex of β-CyD and 5′-AMP at 25°C. Studies at various temperatures allowed for the calculation of thermodynamic parameters.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…Formoso reported similar binding trends with β-CyD through the use of circular dichroism (CD) spectroscopy in a sodium phosphate buffered solution at pH 7. 775,776 Using this method, a 1:1 binding constant of 41 M- 1 was measured for the complex of β-CyD and 5′-AMP at 25°C. Studies at various temperatures allowed for the calculation of thermodynamic parameters.…”
Section: Major Phosphate-binding Functionalitiesmentioning
confidence: 99%
“…1 An examination of the literature reveals that several previous studies have used a range of techniques to demonstrate that inclusion complex formation can occur between b-cyclodextrin and various nucleobases, nucleosides and nucleotides. [16][17][18][19][20][21][22] Early ultraviolet absorption difference spectroscopy studies by Hoffman and Bock showed that bcyclodextrin was only able to interact with two of the six mononucleotides tested, viz. AMP and IMP.…”
Section: (A) Formation Of Host-guest Complexes Via Esi-ms In Both Ft-mentioning
confidence: 99%
“…17 Once again, inclusion complexes containing adenine derivatives were found to have the strongest interactions. In a series of papers, 18,19 Formoso used circular dichroism to investigate the interactions of b-cyclodextrin with various nucleic acid base derivatives. In contrast to Hoffman's studies, inclusion complexes containing guanine, uracil and cytosine derivatives were observed in addition to those containing adenine.…”
Section: (A) Formation Of Host-guest Complexes Via Esi-ms In Both Ft-mentioning
confidence: 99%
“…Ability of -and -CDs to create complexes with nucleic acid monomer units as well as with dinucleoside phosphates resulted in their application as potential probes of nucleic acid structure [94][95][96]. Also the regioselective catalysis of P-O(2,3) bond cleavage in 2',3'-cyclic monophosphates of ribonucleotides by ribonuclease, could be successfully mimicked by -, -or -CDs [97,[90][91][92][93].…”
Section: Unsubstituted Cyclodextrinsmentioning
confidence: 96%
“…The interactions between nucleotides as well as nucleosides and native cyclodextrins were intensively investigated [89][90][91][92][93][94][95][96][97]. Ability of -and -CDs to create complexes with nucleic acid monomer units as well as with dinucleoside phosphates resulted in their application as potential probes of nucleic acid structure [94][95][96].…”
Section: Unsubstituted Cyclodextrinsmentioning
confidence: 99%